Mass flow stability method in the extraction process calculations - Георгиеш, Екатерина Викторовна (Eastern-European Journal of Enterprise Technologies, 2015)
Mass flow stability method, allowing to clarify the existing analytical dependences for calculating the target component withdrawal from the classical-shape bodies (unlimited plate, cylinder, sphere) was proposed. On the example of the III class bodies, application of the method is shown. A mathematical model of the target component extraction from the round particle was developed and the dependence to calculate the concentration was obtained. Consideration of the real body shape deviations from perfect in the form of the shape factor allows to refine the design value for the bodies, corresponding to the III class. It was found that the deviation of the concentration values for the perfect body from real would be the greater, the smaller the particle radius. The maximum relative error of calculations is 11.3 %. It is shown that the target component extraction process is rather complicated and depends strongly on a large number of defining physical characteristics: particle size, diffusion coefficient, mass transfer coefficient, temperature, duration.